Combined HF+MW CVD Approach for the Growth of Polycrystalline Diamond Films with Reduced Bow; Coatings; Vol. 13, iss. 2 - Sedov V. Vadim; Popovich A. Alexey; Linnik S. A. Stepan Andreevich; Martyanov A. Artem; Wei J. Junjun; Zenkin S. P. Sergey Petrovich; Zavedeev E. Evgeny; Savin S. Sergey; Gaydaychuk A. V. Alexander Valerievich; Li Ch. Chengming; Ralchenko V. Victor; Konov V. Vitaly (2023, 2023)
Title screen